2020
DOI: 10.1177/0308022620970861
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of internet-based interventions for women with chronic pain

Abstract: Introduction To evaluate the effects of internet-based interventions on physical and psychosocial outcomes in women with chronic pain through a systematic review. Method A search of the following electronic databases: PubMed/MEDLINE, ScienceDirect, and Web of Science. Two different authors separately tabulated the indices selected in identical predetermined forms. The methodological quality of all randomised trials was assessed using the Cochrane Collaboration’s tool for assessing the risk of bias. Results Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The initial search revealed 309 records, and an additional 20 were retrieved manually from the references. Through the title and abstract screening and the full-text assessment, only four systematic reviews were eligible according to our criteria [6,[13][14][15]. The study screening strategy is shown in the form of a flowchart (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search revealed 309 records, and an additional 20 were retrieved manually from the references. Through the title and abstract screening and the full-text assessment, only four systematic reviews were eligible according to our criteria [6,[13][14][15]. The study screening strategy is shown in the form of a flowchart (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Behavioral modification techniques (BMTs), such as cognitive behavioral therapy, do not necessarily require the therapist to be physically present with the patient [12]. There are several systematic review articles with or without meta-analyses that have addressed this topic, but no research article has provided a general overview of the effect of telematic BMT (t-BMT) with respect to clinical endpoints and variables of interest in patients with chronic pain [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, evidence supports applying PPIs in the treatment of chronic 4 pain [27,28], yet the implementation of PPI approaches into clinical practice has been slow and varied [19,20]. Potential barriers include high patient burden associated with privacy concerns, time, and mobility or travel limitations [18,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear if telematic BMT (e-BMT) is also effective to improve psychological variables and if it is as effective as in-person BMT. Some previous systematic reviews have assessed the effect of telerehabilitation based on BMT on variables such as pain intensity, disability, disease impact, physical function, pain-related fear of movement, and psychological distress [ 9 , 10 , 11 , 12 ], showing promising results.…”
Section: Introductionmentioning
confidence: 99%